Femtosecond fiber CPA system in a single pass configuration - Laskownicki, Michał; Szczepanek, Jan; Stepanenko, Yuriy; Skibiński, Piotr; Wasylczyk, Piotr; Nejbauer, Michał; Radzewicz, Czesław (Photonics Letters of Poland, 2014)
We present a compact Yb-doped fiber chirped pulse amplification system set in a single pass configuration. The system is capable of delivering 34μJ pulses with 200kHz repetition rate. When seeded with a low average power oscillator, the amplifier optical-to-optical efficiency is as high as 37% and the gain reaches 52dB. Temporal pulse degradation due to self-phase modulation is explored. One stage amplification allowed us to limit the set-up complexity, typical for multi-stage CPA systems. Full Text: PDF References J. Limpert et al., "The Rising Power of Fiber Lasers and Amplifiers", IEEE JSTQE 13, 537 (2007). CrossRef D. Strickland, G. Mourou, "Compression of amplified chirped optical pulses", Opt. Commun. 56, 219 (1985). CrossRef A. Klenke et al., "530 W, 1.3 mJ, four-channel coherently combined femtosecond fiber chirped-pulse amplification system", Opt. Lett. 38, 2283 (2013). CrossRef Y. Zaouter, J. Boullet, E. Mottay, E. Cormier, "Transform-limited 100μJ , 340MW pulses from a nonlinear-fiber chirped-pulse amplifier using a mismatched grating stretcher–compressor", Opt. Lett. 33, 1527 (2008). CrossRef L. Kuznetsova, F. Wise, "Scaling of femtosecond Yb-doped fiber amplifiers to tens of microjoule pulse energy via nonlinear chirped pulse amplification", Opt. Lett. 32, 2671 (2007). CrossRef J. Želudevičius, R. Danilevičius, K. Viskontas, N. Rusteika, K. Regelskis, "Femtosecond fiber CPA system based on picosecond master oscillator and power amplifier with CCC fiber", Opt. Expr. 21, 5338 (2013). CrossRef T. Schreiber, C. Nielsen, B. Ortac, J. Limpert, A. Tünnermann, "Microjoule-level all-polarization-maintaining femtosecond fiber source", Opt. Lett. 31, 574 (2006). CrossRef T. Eidam et al., "Femtosecond fiber CPA system emitting 830 W average output power", Opt. Lett. 35, 94 (2010). CrossRef P. Wasylczyk, C. Radzewicz, "Design and alignment criteria for a simple, robust, diode-pumped femtosecond Yb:KYW oscillator", Laser Physics 19, 1 (2009). CrossRef A. Jasik et al., "Low-temperature grown near surface semiconductor saturable absorber mirror: Design, growth conditions, characterization, and mode-locked operation", J. Appl. Phys 106, 053101 (2009). CrossRef O.E. Martinez, "3000 times grating compressor with positive group velocity dispersion: Application to fiber compensation in 1.3-1.6 µm region", IEEE J. Quantum Electron. 23, 59 (1987). CrossRef R. Trebino, Frequency-Resolved Optical Gating: The Measurement of Ultrashort Laser Pulses (Boston, Springer 2000). CrossRef